Effect of systematic nursing intervention on rehabilitation after colorectal polyps of endoscopic removal in children: A protocol for systematic review and meta-analysis. Issue 12 (26th March 2021) - Dong, Zhenyin; Li, Guizhen; Wang, Meigui; Wang, Tingting; Jiang, Chengpeng
Abstract: Background: Endoscopic removal is the main method for the treatment of colorectal polyps in children. Due to the small age of children, poor coordination, postoperative sensitive postoperative response, it is not good for postoperative recovery. Systematic nursing has an advantage in promoting the postoperative recovery of children with colorectal polyps of endoscopic removal, but it is lack of evidence-based basis. The purpose of this study is to evaluate the effect of systematic nursing intervention on the rehabilitation of children after colorectal polyps of endoscopic removal. Methods: China National Knowledge Infrastructure, Wanfang, China Science and Technology Journal Database and Chinese Biomedical Literature Database, PubMed, Embase, Web of Science, and the Cochrane Library databases will be searched by computer. A randomized controlled study is searched on the application of systematic nursing intervention of children with colorectal polyps of endoscopic removal from the establishment of the database in February 2021. The language is limited to English and Chinese. The quality of the included study is independently extracted and the literature quality is evaluated by 2 researchers. The RevMan5.3 software is used to conduct meta-analysis of the included literature. Results: This study will evaluate the effect of systematic nursing intervention on the rehabilitation of children after colorectal polyps of endoscopic removal by the indexes of total effective rate, complication rate, and hospital stays. Conclusion: This study will provide reliable evidence-based basis for establishing a reasonable and effective nursing intervention for endoscopic removal of colorectal polyps in childhood. OSF Registration number: DOI 10.17605/OSF.IO/S57UX.